RNA viruses alter house dust mite physiology and allergen production with no detected consequences for allergenicity. Issue 2 (4th January 2023) - Vidal‐Quist, José Cristian; Declercq, Jozefien; Vanhee, Stijn; Lambrecht, Bart N; Gómez‐Rial, José; Vidal, Carmen; Aydogdu, Eylem; Rombauts, Stephane; Hernández‐Crespo, Pedro
Abstract: RNA viruses have recently been detected in association with house dust mites, including laboratory cultures, dust samples, and mite‐derived pharmaceuticals used for allergy diagnosis. This study aimed to assess the incidence of viral infection on Dermatophagoides pteronyssinus physiology and on the allergenic performance of extracts derived from its culture. Transcriptional changes between genetically identical control and virus‐infected mite colonies were analysed by RNAseq with the support of a new D. pteronyssinus high‐quality annotated genome (56.8 Mb, 108 scaffolds, N50 = 2.73 Mb, 96.7% BUSCO‐completeness). Extracts of cultures and bodies from both colonies were compared by inspecting major allergen accumulation by enzyme‐linked immunosorbent assay (ELISA), allergen‐related enzymatic activities by specific assays, airway inflammation in a mouse model of allergic asthma, and binding to allergic patient's sera IgE by ImmunoCAP. Viral infection induced a significant transcriptional response, including several immunity and stress‐response genes, and affected the expression of seven allergens, putative isoallergens and allergen orthologs. Major allergens were unaffected except for Der p 23 that was upregulated, increasing ELISA titers up to 29% in infected‐mite extracts. By contrast, serine protease allergens Der p 3, 6 and 9 were downregulated, being trypsin and chymotrypsin enzymatic activities reduced up to 21% in extracts. None of the parameters analysed in our mouse model, nor binding to human IgE were significantly different when comparing control and infected‐mite extracts. Despite the described physiological impact of viral infection on the mites, no significant consequences for the allergenicity of derived extracts or their practical use in allergy diagnosis have been detected. Abstract : The infection of the European house dust mite with RNA viruses affects the expression of allergen‐related, immunity and stress‐response genes. Major allergen Der p 23 is upregulated (with ELISA titres increasing in culture extracts), whilst serine protease allergens Der p 3, 6 and 9 are downregulated (trypsin and chymotrypsin activities reduced). No consequences for the allergenic performance of mite extracts have been detected.